Neutralizing Antibody Activity Against the B.1.617.2 (delta) Variant Before and After a Third BNT162b2 Vaccine Dose in Hemodialysis Patients - Benning, Louise; Klein, Katrin; Morath, Christian; Bartenschlager, Marie; Kim, Heeyoung; Buylaert, Mirabel; Reineke, Marvin; Töllner, Maximilian; Nusshag, Christian; Kälble, Florian; Reichel, Paula; Schnitzler, Paul; et al. (Frontiers in Immunology, 2022)
Hemodialysis patients are at high risk for severe COVID-19, and impaired seroconversion rates have been demonstrated after COVID-19 vaccination. Humoral immunity wanes over time and variants of concern with immune escape are posing an increasing threat. Little is known about protection against the B.1.617.2 (delta) variant of concern in hemodialysis patients before and after third vaccination. We determined anti-S1 IgG, surrogate neutralizing, and IgG antibodies against different SARS-CoV-2 epitopes in 84 hemodialysis patients directly before and three weeks after a third vaccine dose with BNT162b2. Third vaccination was performed after a median (IQR) of 119 (109–165) days after second vaccination. In addition, neutralizing activity against the B.1.617.2 (delta) variant was assessed in 31 seroconverted hemodialysis patients before and after third vaccination. Triple seropositivity for anti-S1 IgG, surrogate neutralizing, and anti-RBD antibodies increased from 31/84 (37%) dialysis patients after second to 80/84 (95%) after third vaccination. Neutralizing activity against the B.1.617.2 (delta) variant was significantly higher after third vaccination with a median (IQR) ID50 of 1:320 (1:160–1:1280) compared with 1:20 (0–1:40) before a third vaccine dose (P<0.001). The anti-S1 IgG index showed the strongest correlation with the ID50 against the B.1.617.2 (delta) variant determined by live virus neutralization (r=0.91). We demonstrate low neutralizing activity against the B.1.617.2 (delta) variant in dialysis patients four months after standard two-dose vaccination but a substantial increase after a third vaccine dose. Booster vaccination(s) should be considered earlier than 6 months after the second vaccine dose in immunocompromised individuals.